2006
DOI: 10.1007/s00429-005-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous occurrence of aquaporin-4 in the ependyma and in the circumventricular organs in rat and chicken

Abstract: Aquaporins are selective water channel proteins critical in volume homeostasis. In the CNS AQP4 predominates, localized mainly in the glia limitans, the perivascular endfeet and ependyma. The present immunofluorescent study reveals the distribution of aquaporin-4 in the circumventricular organs in rat and chicken brains. The ventricular ependyma (especially in the third one), the subfornical organ, the area postrema, the rat pineal body (in part), and the vascular organ of lamina terminalis were marked by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 80 publications
6
31
0
Order By: Relevance
“…The colocalization of the AQP4-ir structures with GFAP suggest that this water channel is present in the astrocytic end-feet surrounding the blood vessels and in the astrocytes of the cerebellum. These observations are consistent with previous studies in rat (Nielsen et al 1997;Goren et al 2006) and chicken (Nico et al 2001) in which rat AQP4 antibodies were used. The expression pattern of AQP4 shown in this study is in agreement with the role of this channel in water movement between the brain and cerebrospinal fluid (CSF) compartments, and between the brain and blood (Amiry-Moghaddam et al 2003a).…”
Section: Brainsupporting
confidence: 94%
See 1 more Smart Citation
“…The colocalization of the AQP4-ir structures with GFAP suggest that this water channel is present in the astrocytic end-feet surrounding the blood vessels and in the astrocytes of the cerebellum. These observations are consistent with previous studies in rat (Nielsen et al 1997;Goren et al 2006) and chicken (Nico et al 2001) in which rat AQP4 antibodies were used. The expression pattern of AQP4 shown in this study is in agreement with the role of this channel in water movement between the brain and cerebrospinal fluid (CSF) compartments, and between the brain and blood (Amiry-Moghaddam et al 2003a).…”
Section: Brainsupporting
confidence: 94%
“…Only a few immunohistochemical studies have reported the distribution of AQP4 in the chicken brain by using antibodies to rat AQP4 (Nico et al 2001;Goren et al 2006;Parvas and Bueno 2010). These studies suggest a role of AQP4 in the development and physiology of the bloodbrain barrier (Nico et al 2001;Parvas and Bueno 2010).…”
Section: Introductionmentioning
confidence: 94%
“…20,31 This specific lesion, occurring in the specialized region of the area postrema, shows intense AQP4 expression and has characteristic ''hypendymal'' features; namely, a neurovascular plexus with a loose glial bed, a thin ependymal cover, and an absent blood-brain barrier, which might make the patient vulnerable to attacks. 32 Our observations likely reflect the pathological substrate underlying these clinical and imaging correlates of NMO.…”
Section: Discussionmentioning
confidence: 89%
“…It is interesting to note that chicken AQP4 mRNA levels increased in the hypothalamus, whereas they decreased in the kidney, after 2 d water deprivation [67]. Immunoreactive AQP4 has been detected in circumventricular organs of chicken brain [24]. Recent evidence suggests that AQP4 may have a role in cell migration [63].…”
Section: Aqp4-homologue Channelmentioning
confidence: 97%